Effect of Dietary Allium mongolicum Regel Supplementation on the Quality and Fatty Acid Profile of Beef during Cold Storage - YU Aihuan, WANG Yushan, GAO Huixia, HE Jianjian, SUN Chenxu, XIE Yaodi, YAO Haibo, XU Lei, TAO Wenliang, HU Jinsheng, WANG He, DUAN Yueyan, TANG Defu, LEI Zhaomin, HU Jiang, LIU Wangjing (Shipin Kexue)
Twenty-four Angus cattle were randomly divided into four groups (n = 6). The control group was fed a basal diet, while the experimental groups, LAMR, MAMR, and HAMR, were fed a basal diet supplemented with Allium mongolicum Regel at 10, 15, 20 g per head per day, respectively. The feeding period lasted for 135 days. After completion of the feeding period, the cattle were slaughtered, and samples of the longissimus lumborum muscle were collected for the analysis of meat quality (pH, shear force, color, and textural properties) and fatty acid composition. Additionally, antioxidant capacity, lipid and protein oxidation, and fatty acid nutritional indicators (atherosclerosis index (AI), thrombosis index, hyper/hypo cholesterol ratio, and peroxidation index) were evaluated. The results showed that, compared with the control group, the three experimental groups had significantly lower pH, shear force, and malondialdehyde (MDA) contents (P < 0.05). The LAMR and MAMR groups exhibited significantly lower saturated fatty acid (SFA) content and significantly increased levels of total-antioxidant capacity (T-AOC), glutathione peroxidase (GSH-Px) activity, polyunsaturated fatty acid (PUFA) content, and peroxidisability index (PI) (P < 0.05). The MAMR group showed a significant decrease in atherogenicity value (AV) and AI (P < 0.05). During the cold storage period, the pH, shear force, elasticity, and antioxidant capacity of beef initially increased and subsequently decreased, reaching a peak on the 5th day of cold storage before stabilizing or continuing to decrease. In summary, dietary supplementation with A. mongolicum Regel can reduce the pH and shear force, improve the color, delay textural changes during cold storage, enhance the antioxidant capacity, extend the shelf life, and optimize the fatty acid composition of beef, particularly reducing SFA levels and increasing the levels of PUFA and n-3 fatty acids.